Mobility, Nostalgia, and Ethnic Identity: The Racalmutesi Experience in Canada, and Beyond - Migliore, Sam (Italian Canadiana)

(untitled) (Iter Press, 2021)
We are currently in an era characterized by rapid movement; movement of people, products, resources, and information both within and beyond national boundaries. In this paper, I examine the movement not only of Italians (and more specifically Racalmutesi) to Canada, but also of Canadian Italians to Italy and other locations. As part of this discussion, my aim is to explore the role of nostalgia in people’s conceptions of the interrelationships among movement, ethnic identity, and their sense of “home.”